ANALISIS PROSEDUR PENDAFTARAN PASIEN RAWAT JALAN BPJS IGD GUNA MENUNJANG EFEKTIVITAS PELAYANAN DI RUMAH SAKIT MUHAMMADIYAH BANDUNG - Rismawianty, Tamy Amelya (Jurnal Infokes, 2023)
This study aims to describe the procedures for registering outpatient care at the BPJS IGD to support the effectiveness of services at Muhammadiyah Bandung Hospital. The research method used is a qualitative method with a descriptive approach. Data collection techniques use observation, interviews and questionnaires. From the research results obtained, descriptive analysis of the questionnaire. service time for patient registration was 84%. Meanwhile, the service provider style factor is 81%, which means that these two indicators are effective. However, there are several obstacles that arise, including: 1) There are still patients who do not know about the use of BPJS; 2) There are many BPJS patients who do not know about the registration procedure for outpatient emergency care and patients are still not active in seeking information about registration procedures at the IGD at Muhammadiyah Bandung Hospital. Problem solving efforts that have been made by the hospital to increase the effectiveness of services at the Bandung Muhammadiyah Hospital are: 1) socializing related to BPJS rules in the emergency room for patients; 2) The hospital provides KIUP, so that if there are patients who do not bring KIB, their identity can be found using KIUP. Keywords : Registration Outpatient, Outpatient, Effectiveness of services